Surface Plasmon Resonance (SPR) Simulation of a Gold-Bismuth Bi-layer Gas Sensor - Ulwali, Ruqayah A.; Abbas, Heba Kh.; Karam, Ali J; Al-Zuky, Ali A.; Al-Kadhemy, Mahasin F. Hadi; Al-Saleh, Anwar H. (Iraqi Journal of Science, 2022)
The features of plasmonic surface frequency sensor technology, such as the small number of sensor samples required, electromagnetic interference, and high sensitivity, have been found to be highly important.. In this paper, a simulation program was created in Matlab_b2018 by adopting Fresnel equations for calculating the reflectivity of the electromagnetic wave between different media. A surface plasmon resonance sensor based on electromagnetic wavelengths within the range (100 nm to 1000 nm) has been proposed. The transfer matrix was used for a system consisting of four different media. The first medium is a semicircular BK7 glass prism, the second medium is a gold layer (40 nm thick), then a bismuth layer of variable thicknes(10–80) nm, and the last medium is air as the sensing medium. The surface plasmon resonance (SPR) technique was adopted based on the Kretschmann configuration in the simulation of the proposed system. The simulation results showed that there is no SPR within the range of wavelengths (100-500nm), while SPR appears in the visible region and in the IR region at wavelengths (900 and 1000nm). The SPR phenomenon starts to weaken gradually with an increase in the thickness of the bismuth layer. The full width at half maximum (FWHM) decreases with the decrease of thickness of bismuth layer. The best value for it is (10) at thickness (d=10 nm) and wavelength (900 nm). While the height (H) of the SPR dip increased, with the best value of (0.95) at thickness (d=10 nm) and wavelength (700 nm). Also, the sensitivity increased with increasing the bismuth layer thickness at wavelengths (700 , 800, and 1000 ) nm. The highest obtained sensitivity(S) was (112.5 deg/RIU).